The Ghostly Grounds: Malice and Lunch (A Canine Casper Cozy Mystery-Book 3) - Sophie, Love (Lukeman Literary, 2020)
"The perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads."--Midwest Book Review (For Now and Forever)THE GHOSTLY GROUNDS: MALICE AND LUNCH is Book #3 in a charming new cozy mystery series by bestselling author Sophie Love, author of The Inn at Sunset Harbor series, a #1 Bestseller with over 200 five-star reviews!Marie Fortune, 39, a successful dog groomer in Boston, leaves the stressful life behind and heads to a small town in coastal Maine to create a new life. She remains intent on renovating the old, historic house her great-aunt left her and giving it a new life as a B&B. Yet there was one thing she couldn't plan for: the house is haunted. Two things, actually: her great-aunt also left her a dog-and he is far from a typical dog.When Marie, her reputation for ghost-cleansing growing, is summoned to exorcise an old manor house, she finds more than she bargained for: an unexpected death occurs.Worse, her trusted dog gets so sick, he is sent to the vet indefinitely.Marie, on her own, must solve the murder and expel the ghosts all by herself.Is she up to the task?A page-turning cozy, packed with mystery, love, hauntings, travel, pets and food-anchored around a small town and a B&B in need of renovation that will capture your heart-THE GHOSTLY GROUNDS: MALICE AND LUNCH is an un-putdownable cozy that will keep you turning pages (and laughing out loud) late into the night."The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining."--Books and Movies Reviews (For Now and Forever)
Keywords: Krimi, detektivky